2019
DOI: 10.1177/1357633x18822355
|View full text |Cite
|
Sign up to set email alerts
|

Physical, cognitive and psychosocial effects of telerehabilitation-based motor imagery training in people with multiple sclerosis: A randomized controlled pilot trial

Abstract: Introduction Motor imagery training delivered at home via telerehabilitation is a novel rehabilitation concept. The aim was to investigate the effects of telerehabilitation-based motor imaging training (Tele-MIT) on gait, balance and cognitive and psychosocial outcomes in people with multiple sclerosis (pwMS). Methods This randomized, controlled pilot trial included pwMS and healthy individuals. pwMS were randomly divided into two groups, intervention and control. The intervention group received Tele-MIT twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 36 publications
1
46
0
6
Order By: Relevance
“…The few studies investigating MI in PwMS are mainly limited to considering upper limb actions 13 , 15 , 17 , showing also how cognitive and mood disorders affect MI 28 , 41 , 42 . Only recently the focus has been shifted to lower limb movements 43 45 . Interestingly, evidence indicates that MI has been shown to improve not only walking, but also balance, fatigue, mood and quality of life in MS 43 45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies investigating MI in PwMS are mainly limited to considering upper limb actions 13 , 15 , 17 , showing also how cognitive and mood disorders affect MI 28 , 41 , 42 . Only recently the focus has been shifted to lower limb movements 43 45 . Interestingly, evidence indicates that MI has been shown to improve not only walking, but also balance, fatigue, mood and quality of life in MS 43 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Only recently the focus has been shifted to lower limb movements 43 45 . Interestingly, evidence indicates that MI has been shown to improve not only walking, but also balance, fatigue, mood and quality of life in MS 43 45 . However, to date, it remains unclear whether PwMS show anisochrony between actual and mental locomotion as well and, if so, whether this temporal discrepancy is modulated by spatial constraints 5 , 13 , 15 , 17 and/or affected by cognitive fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…After removing duplicates, 3,115 records were assessed for eligibility. Following the application of inclusion and exclusion criteria and verifying the full-text articles for eligibility, a total of five articles (34)(35)(36)(37)(38) were included in the qualitative synthesis, including two feasibility pilot RCTs and 3 RCTs, as shown in the study flowchart (Figure 1). The mean methodological quality of the five included RCTs, according to the PEDro scale, was 6.8/10 (Table 2), indicating the good overall quality of the included studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…The patients were asked to imagine themselves walking in various manners, accompanied by music and beat, as described by a recent publication ( 42 ). Three studies ( 34 , 37 , 38 ) for MI standardization followed the PETTLEP (physical, environmental, task, timing, learning, emotional, and perspective) approach, which may serve as a viable tool to enhance the effectiveness of an intervention. The PETTLEP model is based on neuroscientific findings, developed by Holmes and Collins, and includes a 7-point checklist of guidelines to follow when devising an imagery intervention ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…MI improves muscle strength in healthy adults [12] and facilitates motor function in people with Parkinson's disease [13]. Moreover, RCTs have shown that MI is effective for people with multiple sclerosis [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%